2008
DOI: 10.1128/aac.00089-08
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Patterns of Genetic Variation at Two Chloroquine Resistance Loci in Worldwide Populations of the Malaria Parasite Plasmodium falciparum

Abstract: Mutations in the chloroquine resistance (CQR) transporter gene of Plasmodium falciparum (Pfcrt; chromosome 7) play a key role in CQR, while mutations in the multidrug resistance gene (Pfmdr1; chromosome 5) play a significant role in the parasite's resistance to a variety of antimalarials and also modulate CQR. To compare patterns of genetic variation at Pfcrt and Pfmdr1 loci, we investigated 460 blood samples from P. falciparuminfected patients from four Asian, three African, and three South American countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
73
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 65 publications
11
73
3
Order By: Relevance
“…Except for a recent report of a single sample from Brazil containing the wild-type CQ-sensitive haplotype CVMNK (55), a significant return of CQ-sensitive parasites has not yet occurred among the MDAQ-resistant populations of SVMNT parasites in South America or in other regions where SVMNT is present and CQ has been either withdrawn or is no longer recommended (56). Consistent with these observations, Mehlotra et al (57) have found that variation in the pfcrt and pfmdr1 loci of Asian and African parasites populations is maintained by substantially different mechanisms than in South American populations where the haplotypes of pfcrt and pfmdr1 both exhibit relatively low levels of diversity. We also note the recent observation of increasingly prevalent SVMNT parasites in Tanzania where AQ pressure has presumably facilitated their spread (51,52).…”
Section: G8supporting
confidence: 74%
“…Except for a recent report of a single sample from Brazil containing the wild-type CQ-sensitive haplotype CVMNK (55), a significant return of CQ-sensitive parasites has not yet occurred among the MDAQ-resistant populations of SVMNT parasites in South America or in other regions where SVMNT is present and CQ has been either withdrawn or is no longer recommended (56). Consistent with these observations, Mehlotra et al (57) have found that variation in the pfcrt and pfmdr1 loci of Asian and African parasites populations is maintained by substantially different mechanisms than in South American populations where the haplotypes of pfcrt and pfmdr1 both exhibit relatively low levels of diversity. We also note the recent observation of increasingly prevalent SVMNT parasites in Tanzania where AQ pressure has presumably facilitated their spread (51,52).…”
Section: G8supporting
confidence: 74%
“…8,21 Evidence of emergence and spread of chloroquine-resistant parasites with CVIET haplotypes from South East Asia to Africa have been documented. 8,21,22 Our single nucleotide polymorphisms findings in isolates from Brazil and Nigeria provide additional evidence supporting the association of SVMNT and CVIET haplotypes respectively with P. falciparum isolates of South American and African origin. However, recent studies from Africa, notably in Tanzania, 3 Angola, 17 and Ghana 22 have reported the presence of SVMNT pfcrt haplotype in parasites from these various areas.…”
mentioning
confidence: 68%
“…8,21,22 Our single nucleotide polymorphisms findings in isolates from Brazil and Nigeria provide additional evidence supporting the association of SVMNT and CVIET haplotypes respectively with P. falciparum isolates of South American and African origin. However, recent studies from Africa, notably in Tanzania, 3 Angola, 17 and Ghana 22 have reported the presence of SVMNT pfcrt haplotype in parasites from these various areas. Although it has been proposed that human migration and the strong commercial relationship between Brazil and Angola could have allowed for the import of the SVMNT haplotype from Brazil to Angola, 17 the same haplotype was found in parasites from Tanzania, 3 a country without strong commercial relationship with South America.…”
mentioning
confidence: 68%
“…Early detection of occurrence and spreading of antimalarial drug resistance would be greatly enhanced by the application of valid antimalarial resistance molecular markers. Among the candidate genes investigated to date, pfcrt mutation is widely acceptable as a reliable marker of chloroquine resistance, while pfmdr1 wild type including number of gene copies strong correlate to mefloquine and artesunate resistance in P. falciparum [15][16][17] . Despite the fact that chloroquine was withdrawn from treatment of falciparum malaria in Thailand for many decades, pfcrt mutation at least at the codon 76 was conserved in all P. falciparum isolates.…”
Section: Discussionmentioning
confidence: 99%